Critical Review of Redefining Diagnostics: The Integration of Laboratory Excellence with Health Administration for Improved Outcomes - Al Garea, Ali Saleh Mohammed; Alqufayli, Mubarak Mohammed Saad; Balharith, Hamad Abdullah Mubarak; Alsagoor, Hadi Fais Mohammed; Al bakri, Ibrahim Abdullah Yahya; Albaltaheen, Dhafer Amer; Alsari, Mansour Ali Gaseem; Alofair, Mohammed Ali Hussein; Almuhamidh, Alhassan Saleh Hadi; Almahmeed, Hadi Saleh Hadi (Journal of Ecohumanism, 2024)
The coupling of lab diagnostics with health administration may become the key pivot point for endorsing health care. Combined with accurate policy formulation and supervisors’ monitoring and control, precision diagnostics can improve disease prevention, management, and patients’ clinical outcomes. This paper aims to review the place of laboratories in health care delivery, the advantages of cooperation, and the difficulty of integration. It underlines key insights, worldwide examples, and new trends as to how laboratory information can be used for planning and decision-making in managing healthcare organizations.